Microbial enrichment on leaf surface and DNA extraction method based on the metagenomics sequencing - Zhang, Yu-han; Fan, Yi; Li, Ting-ting; Pang, Shuang; Liu, Wei; Bai, Ke-yu; Zhang, Xi-mei (2022)
Obtaining high-quality total genomic DNA of microbial community is the basis and difficulty in the study of metagenomics of complex microbial communities. The plant leaf surface is a complex ecosystem with abundant microbial diversity，and the microbial community mediates leaf functional traits and affects plant adaptability. An in-depth understanding of the basic structure and functional principle of the microbial community on leaf surface will contribute to the applications of promoting plant growth and plant protection. Due to the harsh living environment of leaf surface，it is difficult to enrich microorganisms on leaf surface，which severely limits the extraction of high-quality genomic DNA of microorganisms on leaf surface. Based on the existing DNA extraction method，the surfactant Silwet L-77 was added for pretreatment，and the eluent was recycled，which increased the enrichment of microorganisms on leaf surface. The genomic DNA with high purity and concentration was extracted in combination with commercial kit methods. After quality control and library building sequencing as verification，DNA quality met the requirements for metagenomic library construction. This method may improve the enrichment and collection efficiency of microorganisms on leaf surface，increase the success rate of DNA extraction of microorganisms on leaf surface，and provide a reference for applying high-throughput sequencing technology to study the composition of microorganisms on surface and molecular biology research of plants.